Predicting DeKalb County Drug Court Graduation - Holiday, Jeffrey-Michael P (2018)
INTRODUCTION: Substance abuse is a public health problem in the United States. Though substance abuse is a public health issue in the United States, citizens with substance use disorders have a variety of treatment options. Moreover, there is a close relationship between substance abuse and crime. Consequently, due to an overwhelming number of offenders with substance abuse problems, drug courts were created to combat substance use disorders. Though drug courts are effective in combating substance abuse problems, graduation rates from some drug courts are not as high as they could be; this could be due to a range of factors. AIM: The aim of this study was to examine predictors of graduation from a drug court program using demographic data and risk data assessed via the Level of Service Inventory-Revised (LSI-R). The purpose of the study is to discover if race, age, marital status, high school graduation status, drug of choice, and LSI-R scores are predictors of drug court graduation. METHODS: This cross-sectional study included 665 participants from the DeKalb County Drug Court. Data was collected on each participant at intake including the demographic variables, age, race, education, marital status, and primary drug of choice, along with level of psychosocial risk assessed via the Level of Service Inventory-Revised (LSI-R). Logistic regression analyses were used to predict graduation from the Dekalb County Drug Court. RESULTS: The overall DeKalb County Drug Court graduation rate was 45%. LSI-R scores as well as age at entry were both significant predictors of graduating (p < .05) while the variables of race, marital status, drug of choice, and high school graduation status were not. For every one year increase in age of entry, the odds of a participant graduating from the DeKalb County Drug Court increased by 5%. Also, for every one unit increase in LSI-R score, the odds of graduating from the Dekalb County Drug Court decreased by 5%. Graduation rates varied by drug of choice. Only 29.78% (14/47) whose primary drug of choice was an opioid graduated from the DeKalb County Drug Court program, while participants whose drug of choice was methamphetamine were the most likely to graduate with 56.25% (18/32). Crack/cocaine was 2nd highest with 49.49% (97/196) of participants graduating. DISCUSSION: These findings suggest that LSI-R scores and age are predictors of graduation from the DeKalb County Drug Court. Crack/cocaine and methamphetamine were the drugs with highest likelihood of DeKalb County Drug Court graduation, which is inconsistent with previous studies regarding drug of choice and drug court graduation. Race was not a predictor of DeKalb County Drug Court graduation, implying whites and nonwhites graduated from the drug court at similar rates, which is inconsistent with previous research. Additional resources may be needed to help younger clients graduate from drug court. CONCLUSION: Both age and LSI-R scores were predictors of graduation from the DeKalb County Drug Court program. This study has validated the use of the LSI-R as an assessment tool for DeKalb County Drug County entrance. Special interventions may be needed for younger clients to assist them with drug court graduation